The Influence of Work Climate and Job Satisfaction on Employee Performance With Sustainable HR as an Intervening Variable - Fauziah Nur Simamora; Yani Sukriah Siregar; Kaharuddin Kaharuddin (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Achieving the company's strategic vision and mission, where work climate and job satisfaction are crucial factors that influence performance. PT Pertamina Patra Niaga, West Aceh Regency, conditions show that these two aspects have not been managed optimally, resulting in low employee motivation and productivity. To answer this challenge, the research proposes a new approach by integrating the concept of Sustainable Human Resource Management (SHRM) as a mediating variable that is able to strengthen the relationship between work climate, job satisfaction and performance.Purpose: Analyze the influence of work climate and job satisfaction on employee performance with sustainable HR as a variable to support the achievement of the Company's strategic goals, as well as creating a productive and competitive work environment at PT. Pertamina Patra Niaga, West Aceh Regency.Design/methodology/approach: This research uses a quantitative descriptive approach with an explanatory type. Data collection was carried out using questionnaires, observations and interviews with 54 employees. Data analysis using structural equation modeling-partial least square (SEM-PLS) with the SmartPLS program.Findings/Result: Work climate and job satisfaction have a significant effect on employee performance, both directly and through the mediation of Sustainable Human Resource Management (SHRM). SHRM is proven to strengthen these relationships, creating a more stable and sustainable impact on productivity. A high R square value indicates that this model has strong predictability. PT Pertamina Patra Niaga needs to make SHRM an integral part of its management strategy to create an adaptive, innovative and competitive work environment in facing the challenges of an ever-growing industry.Conclusion: Successful employee performance is not only determined by climate and job satisfaction, but also by sustainable HR management. SHRM has proven effective in strengthening overall performance. PT Pertamina Patra Niaga needs to integrate SHRM in management strategies to create adaptive and competitive work systems.Originality/value (State of the art): This research analyzes problems at PT. Pertamina Patra Niaga, to provide insight for companies and employees who face challenges in terms of managing work climate, job satisfaction and employee performance with sustainable HR as an intervening variable Keywords: work climate, job satisfaction, employee performance, organizational behavior, performance assessment